Humanizing Patients: Clinical Applications Based on Physiological Principles - Irfanuddin (HM Publisher, 2019)
The public's perception of the weak competence of health professional actors in Indonesia refers to complaints of lack of communication, empathy, and inadequate medical treatment. When doing therapy to patients, doctors must have a strong scientific basis for understanding basic concepts to improve the structure and function of the human body. This basic concept can be studied through the principles of physiology to be applied in the clinical realm.